DHX34 deficiency triggers tumor-intrinsic immunity via a dsRNA-mediated type I interferon pathway activation in HCC - Chunli Zhang; Limin Huang; Zeyu Li; Qian Wang; Nanbin Liu; Chongyu Zhang; Xi Liu; Chen Zhang; Gaixia He; Jin Sun; Zongfang Li; Hongwei Tian (Neoplasia: An International Journal for Oncology Research, 2025)
Tumors often evade immune surveillance by crippling their immunogenicity in the microenvironment. DHX34, an RNA helicase involved in nonsense-mediated mRNA decay pathway, is critical for aberrant RNA degradation. However, the effect of DHX34 in regulating the immunogenicity in hepatocellular carcinoma (HCC) is still unclear. Here, a surprising function of DHX34 in inhibited HCC immunogenicity is identified. DHX34-deficient tumors were infiltrated by activated T cells that impaired tumor growth and enhanced survival in mice. Mechanistically, DHX34 depletion triggered dsRNA accumulation which may activate cytosolic RNA-sensing pathway effectors such as MAVS, p-IKK, p-IRF3, and the subsequent type-I interferon response, evoking tumor-intrinsic immunity and leading to CD8 T activation. Collectively, DHX34 is implicated as a regulator that orchestrates a barrier in HCC by suppressing dsRNA-driven innate immune activation. Targeting DHX34 may enhance tumor immunogenicity and synergize with immunotherapies, offering a novel therapeutic strategy for HCC.